Stratigraphic column of the Pucará group in the Chinchao secction, Huánuco - Reyes Rivera, Luis (2010)
The stratigraphic column of the Pucara Group in the Cinchao section-Huánuco, shows a thickness of 3,500m. and is predominantly carbonated; it is one of the most complex of this region, being visible its botton and top. It shows three formations: Chambará, Aramachay and Condorsinga The Formation consists of biomicritic, biopelmicritic, intraesparitic, intraesparitic limestones and dolomites with subparalelel laminations, microcalciespheres, chert concentrations,stilolitic structures, lime veins and pyrite traces; its middle part contains interbedding with black and carbonaceous shales. The Aramachay Formation consists of limolitic chalhed margs interbedded with black carbonaceous shales with Arietites of Sinemurian. On its top, hydroterthermal “zebra” shape alterations are visible. The Condorsinga Formation consists of gray biomiccritic. The minning potential is represent for thwe “zebra” structure related to MVT deposits, and the oil potential, for the dark and black mother rocks.